Human p32, interacts with B subunit of the CCAAT-binding factor, CBF/NF-Y, and inhibits CBF-mediated transcription activation in vitro - Chattopadhyay, Chandrani (Oxford University Press, 2004)
To understand the role of the CCAAT-binding factor, CBF, in transcription, we developed a strategy to purify the heterotrimeric CBF complex from HeLa cell extracts using two successive immunoaffinity chromatography steps. Here we show that the p32 protein, previously identified as the ASF/SF2 splicing factor-associated protein, copurified with the CBF complex. Studies of protein–protein interaction demonstrated that p32 interacts specifically with CBF–B subunit and also associates with CBF–DNA complex. Cellular localization by immunofluorescence staining revealed that p32 is present in the cell throughout the cytosol and nucleus, whereas CBF is present primarily in the nucleus. A portion of the p32 colocalizes with CBF-B in the nucleus. Interestingly, reconstitution of p32 in an in vitro transcription reaction demonstrated that p32 specifically inhibits CBF-mediated transcription activation. Altogether, our study identified p32 as a novel and specific corepressor of CBF-mediated transcription activation in vitro.